Understanding the female judoka`s "coach - athlete" relationship: a British perspective - McDonald, K.; Tsukada, M.; Chung, H. (Archives of Budo, 2016)
Background and Study Aim: The initial idea for the investigation came from Maki Tsukada`s two year observation of the British system, but also after reflection on the London 2012 Olympics and the "coach - athlete" interaction. The wider impact of the study will mean that coaches will have a greater understanding of how to build and work at their relationship with their athletes and understand what the important dynamics are within. The purpose of this study was the knowledge about the "coach - athlete" relationship, to gain a greater understanding into the relationship between female judo athletes and their coach.